L’enseignement du kabyle durant la période coloniale et la méthode directe : l’exemple des manuels de Boulifa - Nadia Berdous (OpenEdition, 2020)
This article offers a descriptive analytical reading of Kabyle teaching during the colonial period. We were interested in the Boulifa textbooks developed with the MD imposed in France by the ministerial instructions of 1901. In Algeria, it will be integrated into the teaching programs for French and then to the orals languages as Kabyle.